POLA KOMUNIKASI BRANCH COLLECTION DALAM PROSES PENAGIHAN PEMBIAYAAN BERMASALAH KEPADA DEBITUR / NASABAH PT. BANK MUAMALAT INDONESIA, TBK CABANG BANJARMASIN - Yuda Hertoni; Gt. Irhamni; Sanusi Sanusi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
The purpose of the research to be achieved is to know the process of financing problematic billing to the debtor / customer at PT. Bank Muamalat Indonesia, Tbk Branch Banjarmasin which has been run, to know the communication pattern of Branch Collection in the process of financing problematic billing to the debtor / customer PT. Banak Muamalat Indonesia, Tbk Banjarmasin Branch and to know what attitude changes happened to the debtor / customer when Branch Collection using the communication pattern.This research was conducted on 9 (Nine) informants, 3 (Three) Staff of Branch Collection and 6 (Six) people of debtors / customers. Each is divided into two stages, namely preliminary research and advanced research using structured interview instruments and qualitative methods that are descriptiveThe results of this study resulted in the following conclusions: 1. The process of financing disbursement problem to the debtor / customer at PT. Bank Muamalat Indonesia, Tbk Banjarmasin Branch which has been run by peaceful / kinship through persuasive negotiation with direct communication between Branch Collection with debtor / customer with the aim to find solution together mostly with mechanism of settlement through Restructuring, so until there is currently no settlement through litigation guarantee or through Auction Hall. 2. The communication pattern used by the Branch collection in the collection process to the debtor is the Communication Pattern of Cooperation (cooperation), Accommodation and Contravention, 3. The attitude change that occurs to the debtor / customer is by continuous visits whether the house of the debtor, place of business, workplace, parents, relatives or other relatives, the debtors feel embarrassed, uncomfortable and even disturbed the presence of Branch Collection in billing so that the debtor will be self-conscious to pay.